Penerapan Tata Kelola Teknologi Informasi dan Pengukuran Maturity Level Menggunakan Domain MEA (Monitor, Evaluate Dan Assess) Dengan Framework COBIT (Studi Kasus: Sistem Informasi Akademik AIKOM - Junaidi Sabtu (METIK JURNAL, 2021)
The Academy of Computer Science (AIKOM) Ternate has implemented information technology in the Academic Information System (SIAK) section, which is an important part of connecting management with all stakeholders. Formulation of the problems raised in this study includes how to classify problems into statements that are in accordance with COBIT 5 framework and how to determine and measure the maturity level of IT governance at AIKOM Ternate by using the MEA (Monitor, Evaluate and Assess) domain. The researcher used a questionnaire instrument to measure the maturity level of IT governance at AIKOM Ternate. The sample used was 13 people including the leadership and several staff. Based on the calculation of the maturity level of IT governance, a value for MEA01 (Performance and Conformance) is obtained at 3.2, MEA02 (The System of Internal Control) of 3.3, and MEA03 (Compliance With External Requirements) of 3.3, which means that each subdomain is at level 3, which means Established Process, so that the average MEA maturity level is 3.3, which is in the Established Process status. The results of the recommendations of this study are for MEA01 subdomains need to establish guidelines and SOPs for the implementation of monitoring and evaluation of SIAK, there needs to be monitoring from the leadership of the duties of each stakeholder and set the standard reporting process from data collection, time and feedback from report results. The recommendation for the MEA02 subdomain is that AIKOM Ternate must develop a mechanism for controlling SIAK, develop SIAK quality assurance standards and carry out periodic evaluations of quality assurance. And recommendations for the MEA03 subdomain carry out periodic reviews and make guidelines and SOPs related to SIAK changes based on external changes.